A molecularly imprinted polymers/carbon dots-grafted paper sensor for 3-monochloropropane-1, 2-diol determination. (15th February 2019) - Fang, Min; Zhou, Lv; Zhang, Hu; Liu, Liang; Gong, Zhi-Yong
Highlights: MIPs/CDs grafted paper-based sensor for selective and sensitive determination of 3-MCPD. CDs were intercepted in the paper and MIPs was also directly formed on the paper-based sensor. The composites exhibited high adsorption capacity and excellent selectivity. This method could be applied for the detection of 3-MCPD in soy sauce samples. Abstract: 3-Monochloropropane-1, 2-diol (3-MCPD) is a common food processing contaminant and a simple, rapid, sensitive and low cost monitoring technology is needed due to its potential carcinogenic nature. Carbon dots directly intercepted on filter paper provide high fluorescence intensity and can be adapted for use as a sensor. We synthesized a carbon dot-filter paper in combination with a molecularly imprinted polymeric film to extract 3-MCPD from samples. This grafted paper-based sensor exhibited a high adsorption capacity (68.97 mg g −1 ), an excellent selectivity (imprinting factor = 4.5) and a low detection limit (0.6 ng mL −1 ). Recoveries ranged from 97.2% to 105.3% with relative standard deviations <5.6%. The results obtained using this method were linearly correlated to those of the classic GC–MS method (r = 0.998). Based on the Chinese National Standard, this study provides a novel and powerful platform for the simple, rapid, sensitive and on-site analysis of 3-MCPD in soy sauce.